Subchorionic Hematoma on Threatened Abortion as Risk Factors Occurrence of Spontaneous Abortion - Wijayanti, Ketut R.D. (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To determine whether sub chorionic hematoma increases the risks of spontaneous abortion. Method: Study using prospective cohort design, in which case group was 30 patients with threatened abortion having subchorionic hematoma during 7-20 weeks gestational age (GA), and control group was 30 patients with threatened abortion not having subchorionic hematoma. Diagnosis was confirmed using the aid of ultrasound (USG) (Medison Sondace Live Prime 8000Â®). The sampling method was consecutive sampling of 7-20 weeks GA pregnancy, with minimum CRL measurements 10 mm, who came to obstetrics emergency room or outpatient clinic at Sanglah General Hospital. Patients were followed until 20 weeks GA by physical and USG examination. If the evaluation results were normal, patients were managed as a normal pregnancy. But if it had the same condition as diagnosis for threatened abortion, patients were re-managed as threatened abortion or according to current diagnosis. Result: The average age of patient, gestational age upon examination at first visit and parity of case and control group were not statistically different (p>0.05). Percentage of spontaneous abortion within the case and control group was 40% and 13.33% respectively. The relative risks of spontaneous abortion were three times higher in the threatened group with subchorionic hematoma (RR=3; IK 95% = 1.09-8.25; p=0.02). Median time span of the occurence of spontaneous abortion in the case and control group was 12 and 16 weeks respectively. Conclusion: The risk of spontaneous abortion in threatened abortion with subchorionic hematoma was 3 times higher than those without subchorionic hematoma. [Indones J Obstet Gynecol 2011; 35-4:170-2] Key words: threatened abortion, subchorionic hematoma.